Analysis on the Educational Value of Winter Olympic Spirit in Track and Field Teaching Based on Data Mining under Artificial Intelligence. (7th October 2022) - Yu, Ao; Wang, Jianxing; Zhou, Yixin; Qiao, Xiaoyu; Yan, Song; Feng, Yufang; Marcos, Elvan; Jae, Lee Seok; Fiaidhi, Avera
Abstract : School sports is the basis for the development of mass sports and competitive sports. It goes without saying that the key to the development of school physical education is school physical education, and the teaching of track and field (TAF) courses occupies an irreplaceable position in students' growth education. The stepping stone for the cultivation of sports awareness plays a pivotal role in the better healthy growth of students and the improvement of the physical quality of all citizens. As a major gold medalist in the Olympic Games, TAF is welcomed, valued, and popularized by many countries. Especially in colleges and universities, TAF can cultivate the will of college students and the spirit of continuous improvement. The Winter Olympics (WO), adhering to the spiritual concept of overcoming challenges and facing difficulties, embodies the strength of unity and collective. Based on the current situation of TAF teaching in a university, this paper uses data mining technology to analyze the students' favorite TAF events and their mastery of the WO knowledge and then combines the educational value of the WO spirit to conduct research to explore the teaching significance of the WO spirit to the TAF curriculum.